Design and Development Prototype of Indigenous Robotic Radio Pharmaceutical Dispenser - Menon, Chithra Biju; Siddavatam, Irfan; Bhosale, Vijay (Asian Review of Mechanical Engineering, 2020)
Working in the nuclear medicine department leads to a possibility of long term low level radiations exposure. Imaging technologies like positron emission tomography (PET) and single photon computer tomography (SPECT) requires radiopharmaceuticals to be administered into the patients. There is radiation exposure to the staff especially when they dispense the required radioactive medicine doses with their hands into the syringes from the source vial. Also, during the process there is a possibility of spillage of the radioactive pharmaceuticals which could lead to radioactive contamination. This project aims at automating the steps involved in dispensing the unit doses into the respective syringes from the source vial and placing it in a lead shielded container. This will be achieved by developing a robotic application to carry out the activities. This will reduce the time for which the nuclear medicine staffs is exposed to the radioactive syringe. The only time when he will be exposed will be when it is injected into the patients.